Analisis Ekonomi Alat Pengasap Ikan Tipe Drum Terhadap Pengasapan Ikan Lele (Clarias Sp.) - Asmara, Sandi; Anhar, Satria Radly; Oktafri, Oktafri; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2024)
The purpose of this study is to determine the performance of drum-type fish smokers, determine the economic feasibility value and sensitivity level of drum-type fish smokers to indicators of changes in the number of working days, the price of catfish, and the selling price of smoked catfish. Based on the results of the research, the drum-type fish smoker is able to smoke 6.4 kg of catfish using 1.655 kg of coconut shell and 2.496 coconut fiber as fuel. Based on economic analysis, this tool is declared feasible to use with the BEP value obtained of 22.35/kg, NPV of Rp 72,213,896.97/year, B/C ratio of 1.35 and IRR of 898.25%. Based on the sensitivity analysis of the use of tools to changes in working days, there is no significant change in each change in working days but it is still feasible to run. Based on the sensitivity analysis of changes in the price of catfish, there is a significant change in every change in the price of catfish, where the lower the price of catfish, the more profit is obtained. While the sensitivity analysis on changes in the selling price of smoked catfish occurs a significant change, where the higher the selling price of smoked catfish, the higher the profit obtained from the use of drum-type fish smoking equipment. Keyword: BEP, B/C Ratio, Drum Type of Smoke Fish, IRR, NPV.